Body composition as a marker of performance and health in military personnel - Cialdella-Kam, Lynn; Bloedon, Taylor K.; Stone, Michael S. (Frontiers in Sports and Active Living, 2023)
Introduction Body composition standards are set to ensure operational readiness in active-duty military personnel. To meet body composition standards, some individuals, however, may engage in unhealthy weight control behaviors (i.e., weight cycling and disordered eating). The objectives of this review are to: (1) evaluate the evidence regarding body composition and the associations to physical and military specific performance; (2) discuss body composition and potential health consequences; and (3) examine the evidence of weight cycling and disordered eating behaviors in military personnel for weight control. Methods A systematic search to identify peer-reviewed research articles was conducted in PubMed on 2/20/2023 using Medical Subject Headings (MeSH) including but not limited to “Military Personnel”, “Tactical Athlete”, “Weight Loss”, “Body Composition”, and “Weight Cycling”. Results A total of 225 research articles were identified. The list was narrowed down to articles from the last 20 years (2003–2023) in military personnel. Only studies in which percent body fat was directly measured were included resulting in 17 research articles for this review. Discussion Evidence-based research is limited on the relationship between body composition and operational readiness. Weight cycling and disordered eating behaviors also has been reported for weight control, yet additional research is needed. Specifically, future research should focus on female service members, racial and ethnic differences, age, and postpartum status and include other service branches (i.e., Air Force and Navy). A comprehensive survey on weight cycling, disordered eating, and weight management would be valuable to determine the prevalence and extent of this issue. This information along with performance data would guide policy makers on the relevance and appropriateness of existing body composition standards.